2018
DOI: 10.1148/radiol.2018172099
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of MR Elastography for Liver Fibrosis in Children and Young Adults with a Spectrum of Liver Diseases

Abstract: Purpose To assess the diagnostic performance of magnetic resonance (MR) elastography-derived liver stiffness to detect liver fibrosis in a pediatric and young adult population with a spectrum of liver diseases. Materials and Methods This retrospective study included patients younger than 21 years of age who underwent MR elastography and liver biopsy within 3 months of one another between January 2012 and September 2016 for indications other than liver transplantation or Fontan palliation of congenital heart di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 19 publications
1
79
1
Order By: Relevance
“…One possible explanation is that the presence of hepatic inflammation, which causes swelling of hepatocytes, interstitial edema, and infiltration of inflammatory cells, results in increased apparent liver stiffness . Inflammatory reaction differs according to various chronic liver diseases, including the hepatitis C virus, the hepatitis B virus, autoimmune hepatitis, and steatohepatitis, which result in different apparent stiffness values . Liver stiffness generally consists of elasticity and viscosity, and intrahepatic hemodynamic changes, such as inflammation, congestion, and portal hypertension .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that the presence of hepatic inflammation, which causes swelling of hepatocytes, interstitial edema, and infiltration of inflammatory cells, results in increased apparent liver stiffness . Inflammatory reaction differs according to various chronic liver diseases, including the hepatitis C virus, the hepatitis B virus, autoimmune hepatitis, and steatohepatitis, which result in different apparent stiffness values . Liver stiffness generally consists of elasticity and viscosity, and intrahepatic hemodynamic changes, such as inflammation, congestion, and portal hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…25 Inflammatory reaction differs according to various chronic liver diseases, including the hepatitis C virus, the hepatitis B virus, autoimmune hepatitis, and steatohepatitis, which result in different apparent stiffness values. [10][11][12][26][27][28] Liver stiffness generally consists of elasticity and viscosity, and intrahepatic hemodynamic changes, such as inflammation, congestion, and portal hypertension. [17][18][19] The utility of multifrequency MRE is emerging as an interest for the separation of fibrosis from inflammation of the liver by calculating multiple parameters including loss modulus and damping ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no test results using MRE to analyse liver fibrosis in a cohort of patients with CHC. Two available studies on children and adolescents with CLD who are undergoing MRE and liver biopsy showed excellent accuracy of MRE for detecting significant fibrosis[ 99 , 100 ]. Moreover, by using MR elastography, Trout et al[ 99 ] confirmed the importance of a confounding effect of steatosis or inflammation of liver stiffness values on the example of a subgroup of patients with NFLD.…”
Section: Physical Techniquesmentioning
confidence: 99%
“…For this reason, non-invasive imaging techniques such as ultrasound elastography and magnetic resonance elastography (MRE) are available to assess hepatic fibrosis quantitatively (7). The use of a MRE offers results from larger areas with superior repeatability and reproducibility (8,9). This technique was approved by the U.S. Food and Drug Administration, and is considered an accurate method of evaluating hepatic fibrosis (7).…”
Section: Introductionmentioning
confidence: 99%